2006
DOI: 10.1192/apt.12.3.162
|View full text |Cite
|
Sign up to set email alerts
|

Meeting the mental and physical healthcare needs of carers

Abstract: The health of family carers may affect not only their own lives but also the lives of the people for whom they provide care. This article describes how the caring role can affect the health and well-being of a carer of a person who has a mental or physical disorder. Suggestions are made about how to recognise and ameliorate some of the detrimental effects of the caring role on the carer's own health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 30 publications
3
34
0
5
Order By: Relevance
“…Confirming findings of other researchers (Cormac & Tihanyi 2006), problematic patient behaviors triggered stress reactions in family care-givers who felt a greater need for services to relieve the situation.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Confirming findings of other researchers (Cormac & Tihanyi 2006), problematic patient behaviors triggered stress reactions in family care-givers who felt a greater need for services to relieve the situation.…”
Section: Discussionsupporting
confidence: 84%
“…Under such conditions, caring for a loved one can have detrimental effects on the family care-givers’ physical and mental well-being (Schulz & Sherwood 2008). Multiple studies from North America, Europe and Asia have shown that their duties may increase their physical and psychological morbidity (Cormac & Tihanyi 2006, Pinquart & Sörensen 2003, Schulz & Sherwood 2008). While living with a family member with urgent health needs, family care-givers in privatized health care systems like the one in the United States are at a high risk of not being able to access the services they need (Chaix et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The distressing nature of caring for people with severe mental illness will likely produce elevated levels of anguish in family carers. Previous studies have consistently found that family carers experience higher levels of stress and illness than the general population (Cormac & Tihanyi, ; Hayes et al., ; Oyebode, ). As the findings of this study indicate, family carers will probably experience continual distress as medication typically did not entirely reduce illness symptoms.…”
Section: Discussionmentioning
confidence: 94%
“…Participants respected the need for confidentiality; however, they felt more could be done to share information, respect their views, and to foster a collaborative partnership between the family and the professionals. However, the lack of perceived progress in this area despite UK government guidance (Department of Health, ; Health Offender Partnerships ) and previous research (Cormac & Tihanyi ; Drapalski et al . ; McCann et al .…”
Section: Discussionmentioning
confidence: 99%